A Comparative Study of the Representational Capacity of Three Apex Farmer Organisations in Ghana - Amoako, B.O (University Of Ghana, 2015)
Most Apex Farmer Organisations continually state as part of their mission and objectives that they exist to “represent farmers’ interests and give farmers a voice”; however, most farmers’ have not benefitted much from these Apex Farmer Organisations. The study was structured to assess the representational capacity of three Apex Farmer Organisations in Ghana: Apex Farmer Organisation of Ghana (ApFOG), Ghana Cocoa Coffee Sheanut Farmers’ Association (GCCSFA) and Peasant Farmers Association of Ghana (PFAG); in representing the interests of their primary farmer groups and meeting the expectations of the farmers’. This study used the case study/ survey research methodology with a sample size of 205 farmers and leaders of the Apex organisations within the Central, Eastern and Greater Accra regions of Ghana. Primary data was collected by the use of interviews and questionnaires. Data was analysed using inferential and descriptive statistics. Using the three different dimensions of capacity representation namely: formal, descriptive and participatory representation; the study found that all three organisations have some form of formal representation but are low in participatory representation. However, ApFOG and GCCSFA had a high descriptive representation score than PFAG. Externally, they are all affected by the economy and policy situation of the country. In satisfying the needs of the farmers with regards to certain services, using the Kruskal-Wallis test, GCCSFA ranked highest, followed by ApFOG and then PFAG. It can be recommended that, these three Apex Farmers’ Organisations need to restructure and make their farmers aware of what they do and interact more with their farmers so that the farmers do not have expectations that the Apex organisations cannot meet.
MPhil.
Keywords: Farmer Organisations; Farmers; Farmer Associations; Producer Organisations; Ghana